Takut akan Tuhan sebagai Awal Kebijaksanaan: Kepemimpinan Kristiani menurut Amsal 1:7 - Bala, Gabriel (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
True Christian leadership comes from the Lord Jesus Himself. In Jesus, a Christian leader will lead the people entrusted to him with values and virtues that come from God himself. One of those values and virtues is the